DYSPHORIC MILK EJECTION REFLEX [D-MER] AND ITS IMPLICATIONS FOR POSTPARTUM MATERNAL MENTAL HEALTH: A LITERATURE REVIEW - Wijaya, Dyah Ayu Septika; Nafiati, Dini Latifatun (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2026)
Introduction: Dysphoric Milk Ejection Reflex (D-MER) is a breastfeeding-related phenomenon characterized by brief episodes of negative emotional responses occurring immediately before or during milk ejection. Although it arises from normal neuroendocrine changes in the postpartum period, D-MER may significantly affect maternal mental health and breastfeeding continuation if unrecognized or inadequately managed. Methods: This article is a narrative literature review of published studies on D-MER, postpartum mental health, and breastfeeding. Relevant articles were identified from electronic databases and analyzed to describe clinical characteristics, underlying mechanisms, and implications for mental well-being. Results: The reviewed literature indicates that D-MER is marked by transient dysphoric symptoms, including sadness, anxiety, irritability, and, in some cases, suicidal ideation, which typically resolve within 10-15 minutes after milk ejection. Evidence suggests that D-MER is associated s d with complex biopsychosocial mechanisms, particularly involving dopamine fluctuations and oxytocin-related neuroendocrine pathways that influence mood regulation and stress reactivity. Discuss: These symptoms may negatively impact the breastfeeding experience and contribute to early weaning. D-MER should be distinguished from postpartum depression, as its symptoms are reflexive, short-lived, and temporally linked to breastfeeding outcomes. D-MER represents a distinct postpartum mental health concern requiring increased awareness among healthcare providers. Conclusion: Early identification and appropriate support may prevent more severe psychological complications. Further research is needed to clarify its mechanisms and establish evidence-based management strategies. Keywords: postpartum, mental health, dysphoric milk ejection reflex [D-MER].